2022
DOI: 10.3389/frvir.2022.860872
|View full text |Cite
|
Sign up to set email alerts
|

Changing Finger Movement Perception: Influence of Active Haptics on Visual Dominance

Abstract: The perception of one’s own body is a complex mechanism that can be disturbed by conflicting sensory information and lead to illusory (mis-) perceptions. Prominent models of multisensory integration propose that sensory streams are integrated according to their reliability by approximating Bayesian inference. As such, when considering self-attribution of seen motor actions, previous works argue in favor of visual dominance over other sensations, and internal cues. In the present work, we use virtual reality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On average, the participants correctly identified the pattern played among the 12 patterns 58 % of the time. It is important to note that the participants perceived the pattern essentially as haptic (tactile, through the vibratory stimulation of the controller, and proprioceptive, through the position of their hand and fingers) without any visual indication, although sight remains the main sense in humans in the elaboration of a sensory judgment [7]. Despite the lack of visual information, the participants were successful 58 % of the time compared to 8 % for random choices in identifying the correct pattern.…”
Section: Patterns' Recognitionmentioning
confidence: 95%
“…On average, the participants correctly identified the pattern played among the 12 patterns 58 % of the time. It is important to note that the participants perceived the pattern essentially as haptic (tactile, through the vibratory stimulation of the controller, and proprioceptive, through the position of their hand and fingers) without any visual indication, although sight remains the main sense in humans in the elaboration of a sensory judgment [7]. Despite the lack of visual information, the participants were successful 58 % of the time compared to 8 % for random choices in identifying the correct pattern.…”
Section: Patterns' Recognitionmentioning
confidence: 95%
“…This mechanism is also exploited in clinical XR interfaces addressing phantom limb syndrome in amputee patients (Hunter, 2003;Foell et al, 2014). However, the visual dominance is less prominent during active haptics and self-generated motor tasks (Tsakiris et al, 2006;Rognini et al, 2013;Boban et al, 2022), what highlights the interference with proprioceptive signals, and the need for realistic feedback solutions for sensorimotor trainings. The implications of visuotactile integration in body ownership and out-of-body experience also suggest potential for further avatar therapy, sensibilization, and immersion research (Pavani et al, 2000;Rognini et al, 2013).…”
Section: Haptics and Proprioceptionmentioning
confidence: 99%
“…VR is often characterized by visual dominance and previous work has shown that sense of agency in VR can be altered when the visual feedback provided is incongruent with the participant's actual movements (Salomon et al, 2016). However, more recent work challenges this visual dominance theory with haptic feedback manipulation during multisensory conflicts in VR (Boban et al, 2022). Boban et al found that active haptic feedback paired with congruent proprioceptive and motor afferent signals and incongruent visual feedback can reduce visual perception accuracy in a changing finger movement task in VR.…”
Section: Future Directionsmentioning
confidence: 99%